Tabuh Kutus Lelambatan “Abdi Budaya” - I Gede Mawan; I Putu Tiodore Adi Bawa; I Wayan Diana Putra (Institut Seni Indonesia Denpasar, 2023)
Purpose: This art research and creation aims to produce a tabuh for Kutus Lelambatan with the title “Abdi Budaya” which was presented at the Seke Gong Abdi Budaya, Banjar Anyar Perean Kangin, Baturiti, Tabanan. Methods: The method of creation or steps in the creation of the “Abdi Budaya” uses the art creation method used by two (2) gamelan composers, namely Pande Made Sukerta who composed the Content Ideas, Arranged the Arrangement Ideas and Determined the Arrangements, and I Wayan Beratha consisting of from nguping, menahin, ngalusin dan ngungkab rasa. Aesthetically, the “Abdi Budaya” refers to the style of the papayasang pegongan of Pangkung Village and the ubit-ubitan kekebyaran of Banjar Anyar Perean. Results and discussion: Lelambatan is a form of tabuh from gending pegongan which functions as an instrumental tabuh the context of ceremonies or performing arts. Conventionally there are several types according to the colotomic structure, namely tabuh pisan, tabuh telu, tabuh pat, tabuh nem and tabuh kutus. However, the Tabuh Kutus Lelambatan is very rarely found in Bali considering that its melody cycle is quite long. Long melodies from the tabuh docusus can be accomplished with the